Bastion [large type] - Lackey, Mercedes (Lackey, Mercedes. Collegium chronicles, 2014)
Mags returns to the Collegium, but there are mixed feelings -- his included -- about him actually remaining there. No one doubts that he is and should be a Herald, but he is afraid that his mere presence is going to incite more danger right in the heart of Valdemar. The heads of the Collegia are afraid that coming back to his known haunt is going to give him less protection than if he went into hiding. Everyone decides that going elsewhere is the solution for now. So why not return to the place he was originally found and look for clues? Those who are closest to him, and might provide secondary targets, are going along. With Herald Jadrek, Herald Kylan (the Weaponsmaster's chosen successor), and his friends Bear, Lena, and Amily, they head for the Bastion, the hidden spot in the hills that had once been the headquarters of a powerful band of raiders that had held him and his parents prisoner. But what they find is not what anyone expected.